THE 4th ASCOPE LABORATORY TEST CORRELATION PROGRAMME FOR FUELS BY SAMPLE CODES : A.2/X/82, D.2/Y/82 - Subardjo Pangarso (Scientific Contributions Oil and Gas, 1986)
The properties of commercial products are measured by standardized laboratory test methods to check their Conformance to specification            Two or more measurements of some property of a specific sample by any given test method usually will not givee precisely the same answer.             Therefore, Laboratory test correlation of the specific sample is necessary to be done on the expected precision, accuracy of the test results and the uniformity of interpretative, to step on the credibility of the testing Laboratory.             This is a paper on the conduct and the results of the fourth ASCOPE (ASEAN Council on Petroleum) Cor mellation Programme for fuels were carried out on two kinds of samples.